EFL learners’ code-switching: Why do they switch the language? - Masna, Yuliar (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
This qualitative study aims to figure out the factors that influence EFL learners’ code-switching. In collecting data, a semi-structured interview was conducted which involved five EFL learners as the participants. Those participants were selected through the purposive sampling method: being second-semester students of the English Language Education Department of Universitas Islam Negeri Ar-Raniry, and taking Basic Speaking class. Semi-structured interviewed was applied to collect the data needed. The finding of this study showed that all participants employed code-switching in their class. The reasons for EFL learners’ code-switching were influenced by participants’ roles and relationships, selected topics, and interactions. Thus, code-switching was regarded as a useful strategy that helped the learners convey their ideas to be fully understood and meaningful in the interaction process.